2022
DOI: 10.1371/journal.pone.0276085
|View full text |Cite
|
Sign up to set email alerts
|

In silico functional annotation of hypothetical proteins from the Bacillus paralicheniformis strain Bac84 reveals proteins with biotechnological potentials and adaptational functions to extreme environments

Abstract: Members of the Bacillus genus are industrial cell factories due to their capacity to secrete significant quantities of biomolecules with industrial applications. The Bacillus paralicheniformis strain Bac84 was isolated from the Red Sea and it shares a close evolutionary relationship with Bacillus licheniformis. However, a significant number of proteins in its genome are annotated as functionally uncharacterized hypothetical proteins. Investigating these proteins’ functions may help us better understand how bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 141 publications
0
3
0
Order By: Relevance
“…We conducted a thorough analysis of the 60 HPs utilizing Pfam, InterPro, SUPERFAMILY, SCANPROSITE, SMART, and CATH. The analysis aimed to assign functions to HPs and determine if they exhibited similar functions according to three or more of the aforementioned programs [ 37 , 38 ]. The results showed that 19 HPs had similar functions based on the analysis of multiple programs.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a thorough analysis of the 60 HPs utilizing Pfam, InterPro, SUPERFAMILY, SCANPROSITE, SMART, and CATH. The analysis aimed to assign functions to HPs and determine if they exhibited similar functions according to three or more of the aforementioned programs [ 37 , 38 ]. The results showed that 19 HPs had similar functions based on the analysis of multiple programs.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, most of these variable core genes encoded hypothetical proteins, with the remainder mostly linked to membrane proteins. These genes have often shown variations in response to specific conditions in bacteria (Ijaq et al, 2022; Rahman et al, 2022; Silhavy et al, 2010). This suggests that the observed higher variability in these core genes could indicate constant adjusting of their functionality in response to different conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Some research groups have demonstrated the value of investigating genes coding for hypothetical proteins. For example, Rahman et al identified genes involved in the adaptation of Bacillus paralicheniformis and other genes of potential biotechnological interest among the genes coding for hypothetical proteins (Rahman et al, 2022). In 2020, Araujo et al characterized genes coding for hypothetical proteins that could be involved in the pathogenesis of the bacterium Corynebacterium pseudotuberculosis (Araujo et al, 2020).…”
mentioning
confidence: 99%